NNZ-2566 treatment inhibits neuroinflammation and pro-inflammatory cytokine expression induced by experimental penetrating ballistic-like brain injury in rats - Tortella Frank C; Yao Changping; Waghray Anu; Shear Deborah A; Lu Xi-Chun M; Wei Hans H; Dave Jitendra R (Journal of Neuroinflammation, 2009)
Abstract Background Inflammatory cytokines play a crucial role in the pathophysiology of traumatic brain injury (TBI), exerting either deleterious effects on the progression of tissue damage or beneficial roles during recovery and repair. NNZ-2566, a synthetic analogue of the neuroprotective tripeptide Glypromate®, has been shown to be neuroprotective in animal models of brain injury. The goal of this study was to determine the effects of NNZ-2566 on inflammatory cytokine expression and neuroinflammation induced by penetrating ballistic-like brain injury (PBBI) in rats. Methods NNZ-2566 or vehicle (saline) was administered intravenously as a bolus injection (10 mg/kg) at 30 min post-injury, immediately followed by a continuous infusion of NNZ-2566 (3 mg/kg/h), or equal volume of vehicle, for various durations. Inflammatory cytokine gene expression from the brain tissue of rats exposed to PBBI was evaluated using microarray, quantitative real time PCR (QRT-PCR), and enzyme-linked immunosorbent assay (ELISA) array. Histopathology of the injured brains was examined using hematoxylin and eosin (H&E) and immunocytochemistry of inflammatory cytokine IL-1β. Results NNZ-2566 treatment significantly reduced injury-mediated up-regulation of IL-1β, TNF-α, E-selectin and IL-6 mRNA during the acute injury phase. ELISA cytokine array showed that NZ-2566 treatment significantly reduced levels of the pro-inflammatory cytokines IL-1β, TNF-α and IFN-γ in the injured brain, but did not affect anti-inflammatory cytokine IL-6 levels. Conclusion Collectively, these results suggest that the neuroprotective effects of NNZ-2566 may, in part, be functionally attributed to the compound's ability to modulate expression of multiple neuroinflammatory mediators in the injured brain.